Efficacy of Bio-agents and Phyto-Extracts against Seed Borne Mycoflora of Soybean (Glycine max L.) - Shailesh B. Khodifad; Hemant Sharma (International Journal of Economic Plants)
The present study was aimed to detect and identify seed borne fungi associated with soybean seeds and subsequently determining their effect on seed germination and seedling growth. Seed mycoflora associated with soybean were detected by using agar plate and standard blotter paper method. A total of six fungal species comprising three genera i.e., Aspergillus flavus, Aspergillus niger, Aspergillus versicolor, Fusarium oxysporum, Fusarium pallidoroseum and Macrophomina sp. were isolated from soybean seed. Among these, Fusarium pallidoroseum and Aspergillus flavus were found to be the most prevalent causing considerable reduction in seed germination and seedling growth as compared to control. The effect of different bio-agents and phyto-extracts on seed mycoflora, seed germination and vigour index were evaluated. Trichoderma viride andDhatura leaf extract were found to enhance seed germination, shoot length, root length and vigour index as compared to control.